Blockchain and the ‘Internet of Things' for the construction industry: research trends and opportunities - Elghaish, Faris; Hosseini, M. Reza; Matarneh, Sandra; Talebi, Saeed; Wu, Song; Martek, Igor; Poshdar, Mani; Ghodrati, Nariman (Automation in construction, 2021)
Various applications integrating Blockchain with the Internet of Things (IoT) have emerged in recent years. While industries such as automotive have embraced this integration, application in other areas such as construction remains limited. The scientometric analysis is applied to 648 papers, identifying the use of IoT and Blockchain in engineering, as well as evaluating the progress of research in the construction industry. The qualitative critical review is applied to 88 papers and analyses successful IoT and Blockchain application cases in construction while also highlighting challenges and limitations. Blockchain of Things (BCoT) as a new concept is introduced to exploit the advantages of IoT and Blockchain, and this paper presents potential uses of BCoT in the construction industry. This paper provides researchers with a comprehensive view of related literature and research gaps that offer opportunities for future research. [Display omitted] •648 articles from top-ranked engineering journals on Blockchain and IoT are analyzed deploying scientometric techniques.•The application of Blockchain of Things (BCoT) in the construction industry is critically discussed.•This paper provides a research map for researchers to foster the implementation of BCoT in the construction industry.•Research gaps in blockchain and IoT in construction are identified from an objective viewpoint, as well as a meta-perspective.